Hydraulic calculation of district cooling distribution network - Augusto, Gerardo L. (Animo Repository, 2011)
Variable primary flow pumping in chilled water system was used as a benchmark to calculate the theoretical system pressure drop of the distribution network. The system of nonlinear equations consisted of pump performance curve and system of characteristic curves of distribution network with twelve (12) energy transfer stations (ETS).Multi-variable Newton-Raphson and Singular-Value Decomposition methods were used in solving the nonlinear equations. Method of Least Squares and Cholesky Decomposition were adapted to derive new sets of pump characteristic curves taken from Similarity Laws considering that pumps are modulated at its best efficiency point.